1997
DOI: 10.1097/00007890-199711270-00024
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Immunoglobulin A Nephropathy After Renal Transplantation

Abstract: Recurrent IgAN is a clinically relevant problem in renal transplant patients. Its importance may have been underestimated in the past due to inadequate lengths of follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
55
1
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(61 citation statements)
references
References 4 publications
4
55
1
1
Order By: Relevance
“…Therefore, an alternative explanation for the effects of LTβR-Ig on IgAN may be reduced GVHD or colitis mediated by LTβR-IG treatment, and specific involvement of gut IgA production needs to be further elucidated. In 60% of IgAN patients that undergo renal transplantation, the disease recurs in the transplanted kidney (43). Our results suggest an important application for LTβR-Ig in the treatment of IgAN.…”
Section: Discussionmentioning
confidence: 68%
“…Therefore, an alternative explanation for the effects of LTβR-Ig on IgAN may be reduced GVHD or colitis mediated by LTβR-IG treatment, and specific involvement of gut IgA production needs to be further elucidated. In 60% of IgAN patients that undergo renal transplantation, the disease recurs in the transplanted kidney (43). Our results suggest an important application for LTβR-Ig in the treatment of IgAN.…”
Section: Discussionmentioning
confidence: 68%
“…Similarly, Ohmacht and coworkers previously reported that recurrence was frequent in patients who had rapid progression to ESRD and IgAN diagnosed by biopsy. 13 However, there was no difference in recurrence rates within the same age groups, according to period of progression to ESRD. The recurrent group of patients aged ≥ 20 years showed rapid deterioration from PS to RRT (23.4 vs 58.1 mo; P = .051) with poorer renal function than patients who had no recurrence, but statistical significance was not observed.…”
Section: Discussionmentioning
confidence: 85%
“…3 However, other investigators did not find a similar relation, and further studies about recurrence are required to corroborate or refute the finding. [11][12][13] In addition, there are no comparative data about recurrence according to age.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the largest series (nΩ104, median follow-up of 5 years) clinical recurrence occurred in only 12.5% (315). Of those with recurrent disease, graft failure occurs in 6-33% (283,300,308,309,(311)(312)(313)(314)(315). A shorter interval between onset and ESRD appears to correlate with recurrent disease (314,315).…”
Section: The Evaluation Of Renal Transplant Candidates: Clinical Pracmentioning
confidence: 93%
“…The incidence of histologic recurrence has been shown to increase with duration of follow-up after transplantation (308). Clinical recurrence (variously defined) has been reported in most studies to be 20-40% (273,275,278,283,300,(308)(309)(310)(311)(312)(313)(314)(315). However, in the largest series (nΩ104, median follow-up of 5 years) clinical recurrence occurred in only 12.5% (315).…”
Section: The Evaluation Of Renal Transplant Candidates: Clinical Pracmentioning
confidence: 99%